(untitled) (Configurazioni. Research on contemporary poetry, 2022)
The paper addresses the question of the transgenerational by analysing a selection of writings by Osip Mandel’štam (1891-1938), Paul Celan (1920-1970), and Durs Grünbein (1962). The work suggests that the «unconscious of the text» (André Green) of these poets is permeated by a concern for the dynamics of transmission. In these terms, poetry can be interpreted as a space of survival of an absence, which represents a source of resignification of a possible encounter between distant generations in time and space.